TRADE UNIONS IN THE INDEPENDENT STATES OF CENTRAL ASIA AND THE CAUCASUS: PRESENT STATE, PROBLEMS, AND PROSPECTS - ERGASHEV, Bakhodyr (CENTRAL ASIA AND THE CAUCASUS, 2011)
The trade unions that operate in the independent states of Central Asia and the Caucasus have had to adjust to the world financial and economic crisis and its repercussions, rising unemployment, increasing informal employment, illegal trade migration, etc. They must show more efficiency when dealing with social and labor conflicts, find new and more efficient forms of cooperation between employers and employees, and learn to coordinate their efforts.The events which shook the world trade union movement in 2008-2011 (trade unions were actively involved in the revolutions in Tunisia and Egypt; mass riots; the nationwide strike and protest movements in Greece; demonstrations in Australia caused by the financial crisis; and strikes in Russia) show that trade unions must readjust their goals, formulate new tasks, and create new technologies. The events of 2007-2010 in Central Asia and the Caucasus, caused, in particular, by the financial crisis in Kazakhstan (large-scale strikes of workers who demanded that some enterprises should be nationalized, which forced the authorities to retaliate), showed that changes were long overdue.Today, the trade union movement in both regions is a conglomerate of monopolist trade unions which actively cooperate with the authorities, on the one hand, and small alternative and independent structures, on the other.The monopolists1 inherited their well-known faults from the Soviet trade unions; they are never invited to discuss draft laws and state budgets or to attend the hearings of the executive structures, etc. Alternative and independent trade unions are much less developed in Kazakhstan, Georgia, and Kyrgyzstan than, for example, in Belarus. There is any number of scholarly publications dealing with the trade union movement in the post-Soviet expanse in 2008-2011.2 The Central Asia and the Caucasus journal publishes articles dealing with the roles of independent trade unions, the forms and methods of their activities, and their possible prospects.3